Electrocaloric effect, pyroelectric response and energy storage performance of lanthanum-modified PZT relaxor ferroelectric ceramic - Pérez-Martín, Y.; Peláiz-Barranco, A.; García-Zaldívar, O.; Calderón-Piñar, F.; Yang, Tongqing; Paiva, P. M. [UNESP]; Silva, A. C.; Guerra, J. D.S. (Elsevier, 2023)
Pb0·85La0·10Zr0·60Ti0·40O3 ferroelectric ceramic system was synthesized via the conventional solid-state reaction sintering route. A systematic study on the pyroelectric response, electrocaloric effect and energy storage properties has been carried out in a wide temperature range, in order to explore its multifunctional features. The obtained results from X-ray diffraction technique, performed at room temperature, revealed the coexistence of two ferroelectric phases governed by the tetragonal (P4mm) and monoclinic (C1m1) symmetries. The pyroelectric behavior of the studied sample has been analyzed by the static method, from the temperature dependence of the pyroelectric current. The electrocaloric response as well as the energy storage performance have been investigated from the ferroelectric hysteresis loops (P−E curves), at 50 kV/cm, covering a wide temperature range. The obtained results revealed a ferroelectric ceramic composition with suitable properties and strong potential to be used in multifunctional electronic devices based on pyroelectric sensors combined with high efficiency energy storage performance and solid-state refrigeration technologies.
Keywords: Ceramics; Electrocaloric effect; Ferroelectrics; PLZT; Pyroelectrics